PANIS: Check it out! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Pacific Animal Health Information System or PANIS is a database and information system available on the Internet and on CD-ROM (only for Pacific Island Countries participating in PANIS)